2020
DOI: 10.3390/agronomy10050693
|View full text |Cite
|
Sign up to set email alerts
|

Rootstock and Arbuscular Mycorrhiza Combinatorial Effects on Eggplant Crop Performance and Fruit Quality under Greenhouse Conditions

Abstract: The herbaceous grafting of fruiting vegetables is considered a toolbox for safeguarding yield stability under various distresses and for improving fruit quality. Inoculation with arbuscular mycorrhiza (AM) fungi seems also to be an efficient tool for increasing the assimilation, uptake and translocation of macroelements and microelements, for modulating plant secondary metabolism and for overcoming several forms of plant distress. The present work evaluated the combined effect of grafting the “Birgah” (B) eggp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 56 publications
0
17
0
1
Order By: Relevance
“…Plant biostimulants are a group of compounds and/or microorganisms which represent a novel sustainable tool to enhance plant performance, yield and fruit quality under stressful or no-stressful cultivation conditions [8][9][10][11][12][13][14][15][16][17]. Rouphael et al [18] and Rouphael and Colla [19] found that biostimulants ameliorate plant responses, such as nutrient use efficiency (NUE), stress tolerance, fruit features and nutrient uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Plant biostimulants are a group of compounds and/or microorganisms which represent a novel sustainable tool to enhance plant performance, yield and fruit quality under stressful or no-stressful cultivation conditions [8][9][10][11][12][13][14][15][16][17]. Rouphael et al [18] and Rouphael and Colla [19] found that biostimulants ameliorate plant responses, such as nutrient use efficiency (NUE), stress tolerance, fruit features and nutrient uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, an increase of the antioxidant activity was also recorded (WMD: +0.94; 95% CI: +0.19, +1.70; I 2 = 74%; P = 0.01). [152][153][154][155][156][157][158][159][160], and plotted according to the mean difference. The weight of each study is represented by the size of the green box.…”
Section: Influence Of Pgpm Inoculum In Improving Nutritional and Nutraceutical Aspects On Fruitsmentioning
confidence: 99%
“…Heterogeneity was assessed using I2 statistical test that represents the amount of total variation that could be attributed to heterogeneity. [152][153][154][155][156][157][158][159][160], and plotted according to the mean difference. The weight of each study is represented by the size of the green box.…”
Section: Influence Of Pgpm Inoculum In Improving Nutritional and Nutraceutical Aspects On Fruitsmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantages for the plant resulting from the interaction with an AMF are, however, not only an improved nutrient supply but also increased resistance against pathogens, and improved tolerance to water and salt stress and to pollutants [ 10 , 11 , 12 ]. Other well-described positive effects of AM are an early onset of flowering and an increased yield and number of marketable fruits [ 13 , 14 , 15 , 16 , 17 ]. As a consequence, AMF are more and more integrated into plant production systems, as they contribute to a reduction of chemical fertilizers and pesticides.…”
Section: Introductionmentioning
confidence: 99%